2021
DOI: 10.3390/coatings11091025
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Data Collection Device for Plasma Equipment Intelligence Studies

Abstract: In this study, various diagnostic tools were constructed and plasma factors measured to evaluate the intelligence of plasma process equipment. We used an ICP (Inductively Coupled Plasma) reactor with a radio frequency (RF) power of 13.56 MHz, a power of 400 to 800 W, and a pressure of 10 to 30 mTorr. Plasma parameters such as electron density (ne), electron temperature (Te), plasma potential (Vp), and floating potential (Vf) were measured using several instruments (VI probe and mass/energy analyzer, etc.) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The process gas was N 2 (99.999% purity) and the flow rate and pressure were controlled using a mass flow controller (MFC, Mass-Flo ® , 1000sccm, MKS, Andover, MA, USA). The reactor base pressure was 10 −6 Torr, which was maintained using a turbomolecular pump (STP-1303C, Edwards, Burgess Hill, UK) and dry pump (GX100N, Edwards, Burgess Hill, UK) [10]. The cut-off probe (CP) and Langmuir probe (LP) were measured 200 mm from the center of the chamber and 20 mm from the wafer surface.…”
Section: Methodsmentioning
confidence: 99%
“…The process gas was N 2 (99.999% purity) and the flow rate and pressure were controlled using a mass flow controller (MFC, Mass-Flo ® , 1000sccm, MKS, Andover, MA, USA). The reactor base pressure was 10 −6 Torr, which was maintained using a turbomolecular pump (STP-1303C, Edwards, Burgess Hill, UK) and dry pump (GX100N, Edwards, Burgess Hill, UK) [10]. The cut-off probe (CP) and Langmuir probe (LP) were measured 200 mm from the center of the chamber and 20 mm from the wafer surface.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there have also been studies about the correlation between plasma parameters and electrical parameters obtained by VI probe. Kim et al [10] analyzed the correlation between plasma parameters and the data obtained by VI probe in inductively coupled plasma reactor using N 2 gas. They observed that a plasma density and a plasma temperature were strongly correlated to the difference between a plasma potential and a floating potential.…”
Section: Introductionmentioning
confidence: 99%